(untitled) (Al-Qamar, 2018)
It is a common problem of the society that people stockpile grain and other items for profit. Due to non-availability of these things the needy face trouble and on the other hand society suffers from inflation and various other economic problems. Due to the catastrophic economic losses of hoarding the Quran and Sunnah strictly forbid it. But people generally do not pay attention to this issue which is often due to their unfamiliarity with the Sharīʻah principles and the investigations of Islamic scholars and jurists in this regard. Keeping in view this context, the present article seeks to clarify the relevant rules of the Quran and Sunnah and the interpretations of the scholars. It finds that all kinds of hoarding are unlawful or at least hateful according to Sharīʻah.